HUBUNGAN ANTARA KEKUATAN MENGGENGGAM DENGAN NYERI MUSKULOSKELETAL PADA PEKERJA BANGUNAN PERUSAHAAN X - Umi Salamah, (2023)
Background: Building construction workers are one of the sectors that have a high prevalence of musculoskeletal disorders. Risk factors related to musculoskeletal disorders in construction workers are mechanical, occupational, and psychosocial factors. Building construction workers are required to have a high level of muscle strength, especially in hand muscles or handheld muscles to fulfill several tasks and workloads according to their fields based on experience and work methods. Objective: This study was to determine the relationship between grasping strength and musculoskeletal pain in construction workers of company x. Method: The method used in this research design is a correlational quantitative research method with a cross sectional approach. The measuring instrument used to measure gripping strength is a handgrip dynamometer and to measure musculoskeletal pain using a Nordic Body Map questionnaire. The sample size in this study was 45 construction workers in company x who were selected according to inclusion and exclusion criteria. Results: Based on the results of data processing using SPSS 25.0, it was found that as many as 34 of the 45 research samples were included in the low-risk category of experiencing MSDs with a percentage (75.6%) and the rest were included in the moderate level category after a correlation test obtained a correlation coefficient of Spearman's Rho MSDs with the strength of grasping the right hand p = - 0.336 with a significance value of p = 0.024, and correlation coefficient of Spearman's Rho MSDs with a left gripping power p = -0.318 with a significance value of 0.033. Conclusion: The conclusion obtained based on this study is that there is a relationship between grasping strength and musculoskeletal pain in company x construction workers.